Impacto del Estiramiento Analitico del Cuadriceps en la prevencion de la tendinopatia rotuliana en deportistas del Club Deportivo el Rosal y Amjuba de la provincia de Bolivar 2018-2019 - García Palomino, Gustavo Adolfo (2019)
The present study was conducted to a total of 40 semi-professional basketball players from the Ambjuba and El Rosal Sports Clubs in the Juvenile and Senior categories of the Province of Bolivar belonging to Ecuador, in which it was found that the effects of stretching technique of cuadriceps for the prevention of patellar tendonitis. This technique was applied for one month in the players and in turn a pre and post test was performed to know the intensity of the discomfort, using the visual scale of Eva pain and the VISA-P scale. These scale tools allow to measure the functional effectiveness of the patellar tendon. Finally, quadriceps stretching is effective in the prevention of patellar tendinitis, since it reduces pain intensity and improves the functionality of the tendon in basketball players.